Clusters – Typology and Public Policy - Li, Ruomu; Yip, Vincent; Dobrzański, Paweł (Klastry – typologia i polityka publiczna, 2023)
Clusters, especially high-tech, are important economic phenomena in modern society. As the archetype, Silicon Valley drives governments over the world to initiate their own cluster. Likewise, the cluster policy has also become a major policy tool in the urban planning field. Based on approaches to initiate and promote clusters, the current cluster policy can be divided into three models, the American model, the Asian model, and the European one. This paper focuses on the sustainability of clusters, reviews the literature about high-tech clusters, cluster policy, and the developments of selected clusters, including Silicon Valley, Silicon Fen, Hsinchu Science Park, Singapore Science Park and One-North, and Akademgorodok; discusses their developments and challenges, and aims to explore the role of government and possible approaches. Based on the data analysis, the research concluded that governments are essential to a cluster’s sustainability. The approach of mixing bottom-up and top-down intervention might be the final direction for all countries, and the only difference lies in timing, which varies with local resources, social environments, and especially culture. For governments, its role should be identifying the right timing to implement the adaption in policy, coordinate, and lead the battle for sustainability in practice.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 3, s. 38-51
Keywords: cluster; Silicon Valley; Silicon Fen; Singapore Science Park; public policy; urban planning; klastry; polityka publiczna